تدوير العمل ودوره في التغلب على الاحتراق الوظيفي لدى المساعد الإداري في مدارس المرحلة المتوسطة بشرق جدة - العتيبي، منال جزاء; الصائغ، نجاة محمد سعيد (المركز القومي للبحوث غزة, 2024)
هدف البحث إلى التعرف على تدوير العمل ودوره في التغلب على الاحتراق الوظيفي لدى المساعد الإداري في مدارس المرحلة المتوسطة بشرق جدة، ولتحقيق أهداف البحث؛ استخدمت الباحثة المنهج الوصفي، وقد استخدمت الاستبانة أداة لجمع البيانات؛ إذ طبقت على عينة عشوائية من المساعد الإداري في مدارس المرحلة المتوسطة بشرق جدة، بلغت (96)، وتوصل البحث إلى مجموعة من النتائج منها: أن واقع تدوير العمل على المساعد الإداري في مدارس المرحلة المتوسطة بشرق جدة، جاء بدرجة مرتفعة وبمتوسط حسابي قدره (3.24)، وأن هناك علاقة سلبية ضعيفة بين تدوير العمل والإنهاك العاطفي، وفقدان العنصر الإنساني لدى المساعد الإداري في مدارس المرحلة المتوسطة بشرق جدة وهناك علاقة إيجابية ضعيفة بين تدني الإنجاز الشخصي لدى المساعد الإداري، وأن هناك أثرا ذا دلالة إحصائية لتدوير العمل في التغلب على الاحتراق الوظيفي لدى المساعد الإداري في مدارس المرحلة المتوسطة بشرق جدة، بأبعاده الثلاثة، ويعني ذلك أن تطبيق تدوير العمل يقلل من الاحتراق الوظيفي، وتمثلت توصيات البحث في: أنه على وزارة التعليم أن تهتم بالمساعد الإداري، وتعمل على تخفيف شعوره بالاحتراق الوظيفي من خلال التطبيق الجاد والصحيح لسياسة تدوير العمل للتغلب على الروتين والركود في العمل، وتجديد بيئة العمل، وأن تقوم الوزارة بتنفيذ برامج تدريبية لقائدات المدارس، تؤهلهن إلى التعرف على أعراض الاحتراق الوظيفي، والأسباب التي تؤدي إليه، ومحاولة القضاء عليها من خلال تطبيق تدوير العمل وضرورة إلمام قائدات المدارس بما يمر به المساعد الإداري من ضغوط في العمل قد تسبب له الوقوع في الاحتراق الوظيفي. وضرورة تنفيذ برامج إرشادية، ووقائية وعلاجية للمساعد الإداري تمكنهم من التغلب على الاحتراق الوظيفي بشكل عام، والكشف المستمر عن الاحتراق الوظيفي لدى المساعد الإداري من خلال استخدام المقاييس الفعالة كمقياس ماسلاش. The research aims to identify work rotation and its role to get rid of job burnout at the administrative assistant in middle stage schools at east of Jeddah and to accomplish the objectives of the research, The questionnaire was used as a tool for collecting data, as it was applied to a random sample of (96) administrative assistants in middle school schools in eastern Jeddah, and the research concluded a group of the outcomes such as: the reality of work rotation to the assistant administrative at the intermediate stage at the schools of east of Jeddah was come in a high degree, and with an arithmetic average rated (3.24), that means there is a weak negative relationship between work rotation and the emotional exhaustion and the loss of the human element with the assistant administrative at the intermediate stage at the schools of east of Jeddah, there was a weak positive relationship between the low personal achievement of the assistant administrative, and there was an effect with statistical evidence for work rotation to get rid of the job burnout with the assistant administrative at the intermediate stage at the schools of east of Jeddah with its three dimensions, and this means that the application of work rotation reduces the job burnout and there were concluded the recommendations: the ministry of education should be interested with the assistant administrative and works to relieve his feeling of job burnout through the hard and proper application of the policy of work rotation to get rid of routine and recession at work and to renew work environment, and the ministry should make training programs to the principals of schools to qualify them to identify the symptoms of job burnout and its reasons, and a trial to get rid of it through application of work rotation, and to be an experience by the schools principals regarding the circumstances of assistant administrative such as work pressure that may cause job burnout creation guiding, protective and treated programs to the assistant administrative to enable them to get rid of job burnout generally, and the continuous detection of job burnout with the assistant administrative through using the effective measurements such as Cristina Maslach.
Keywords: التدوير الوظيفي -- الاحتراق المهني -- المؤسسات التربوية -- السعودية